Popular Music as Public Health Technology: Music for Global Human Development and “Giving Voice to Health” in Liberia - Frishkopf, Michael (Journal of folklore research, 2017)
This article presents an applied ethnomusicological approach to public health promotion, showing how mediated popular music can support better sanitation behavior, by outlining a pilot project conducted in post-conflict Liberia. This approach centers on amethodfor effective, sustainable, empowering, and ethical collaboration and atheoryfor positive behavioral change. The method is Participatory Action Research (PAR), a powerful model for applied, collaborative ethnomusicology. The PAR model radically revises the relationship between “researcher” and “researched,” combining committed, egalitarianparticipation, transformativeaction, and appliedresearchaimed at positive, sustainable social change, in a continuous spiral of planning, acting, observing, and reflecting. The theory is the social psychological notion of “reasoned action” (Fishbein and Ajzen 1975), as applied to public health by Hubley (1984; 1988; 1993) to underscore the combined roles of beliefs, values, and subject norms to influence behavioral intentions toward health. I augment this theory, highlighting music's affective potential for shaping belief, value, and subject norms. Taken together, theory and method support what I call “human development,” defined as progress toward collaboratively-set humanly-oriented objectives, via grassroots, egalitarian, empowering collaborations. The pilot project is enacted by a far-flung PAR network, including nationals of Liberia, the USA, and Canada, connecting creative music/video production, ethnomusicology, public health, and development. Project outputs include a music video and a documentary video, linked through common sounds, images, and purpose. Each is “double-sided,” seeking to change behavior in both the developing and developed worlds. The article assesses project limitations and charts strategies to address them in the future.